Sketches of the New Mining District at Sullivan, Maine - C. W. Kempton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
IF New England were located in some distant and almost inaccessible region, there is no doubt that its mineral resources would have been ere this well developed and generally acknowledged, but laboring under the disadvantage of nearness, it has been neglected. Its surface, moreover, is not cut up by mountains and canons, and the remnants of many of the old ridges are extensively covered by glacial drift. Having for the past ten months been engaged in the development of a. mineral district in Southeastern Maine, I would take this opportunity to lay before the Institute sketches of results, and try to give some idea of the formations as found. The Sullivan Mining District extends from the town of Franklin, through Hancock, Sullivan, and Gouldsborough, from northwest to southeast, about sixteen miles. A general idea of this locality may be gathered from the map accompanying. (Fig. 1).